Pendampingan pembuatan alat pengering ikan untuk nelayan di Kawasan Pantai Gresik - Rohmannudin, Tubagus Noor; Sulistijono, Sulistijono; Satrianugraha, Rifqi Fernady (Tintamas: Jurnal Pengabdian Indonesia Emas, 2025)
The objective of this community engagement activity is to support the improvement of the economic well-being of coastal fishermen in the Gresik area. This initiative is based on the need to preserve fish by reducing its moisture content, thereby inhibiting the growth and proliferation of bacteria (microorganisms) and extending the shelf life of the fish. One of the most common preservation methods is drying. Traditionally, fish drying is conducted using direct solar exposure. However, this method is unhygienic, as the fish is exposed to contamination from insects, birds, and other animals. Additionally, it is prone to dust and cannot be carried out during rainy conditions, which delays the drying process and affects productivity. These challenges have led to the idea of designing and developing a fish drying device using an indirect active solar drying method. Therefore, the Corrosion and Battery Laboratory of the Department of Materials and Metallurgical Engineering, Faculty of Industrial Technology and Systems Engineering (DTMM FTIRS – ITS), took the initiative to carry out a community service program focused on the development of a fish drying device through a participatory-collaborative mentoring approach with fishermen in the coastal area of Gresik. As a result of this program, a functional fish drying device was produced, and the local fishermen are now able to utilize it effectively.